Co-operatives sustainability from the resource-based view perspective / Nooraslinda Abdul Aris, Norashikin Ismail and Roslani Embi - Abdul Aris, Nooraslinda; Ismail, Norashikin; Embi, Roslani (Faculty of Accountancy, 2019)
Co-operatives provide enduring solutions to the national economic challenges confronting society. The Malaysian co-operatives however, are faced with issues on size, capital, structure, networking, management, and governance which resulted in poor performance. Many attempts have been seen to enhance the capacity and capability of co-operatives towards nation building especially after the pronouncement of the International Year of Co-operatives in 2012 which includes the Sustainable Development Goals (SDGs) proposal by the United Nations. Although the core values have been well identified but guidance to remain sustainable in the global environment is absent. This paper, therefore, aims to determine the drivers of sustainable performance based on the resource-based view (RBV) for the co-operatives to remain competitive and relevant. Content analysis is used to construct the unique resources and capabilities poses by the co-operatives alongside with suitable sustainability elements. The quantitative data were collected during focus group sessions held between March and June 2017. The findings revealed that the facets of dynamic and entrepreneurial capabilities are significantly affects the sustainable performance of Malaysian co-operatives. The study contributes towards enriching the knowledge of the relationship between RBV and sustainability and its influence towards the co-operative performance; whereby empowering co-operatives to contribute towards nation building.